2014
DOI: 10.1021/ja4107176
|View full text |Cite
|
Sign up to set email alerts
|

Reverse Micelles As a Platform for Dynamic Nuclear Polarization in Solution NMR of Proteins

Abstract: Despite tremendous advances in recent years, solution NMR remains fundamentally restricted due to its inherent insensitivity. Dynamic nuclear polarization (DNP) potentially offers significant improvements in this respect. The basic DNP strategy is to irradiate the EPR transitions of a stable radical and transfer this non-equilibrium polarization to the hydrogen spins of water, which will in turn transfer polarization to the hydrogens of the macromolecule. Unfortunately, these EPR transitions lie in the microwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(77 citation statements)
references
References 53 publications
2
75
0
Order By: Relevance
“…In addition to classic structure determination, the reverse micelle NMR systems offer a range of benefits in biophysical studies of proteins and nucleic acids such as hydration, temperature and pressure dependent phenomena, ligand binding, confined space effects and so on. The recent observation of substantial nitroxide-mediated dynamic nuclear polarization of the reverse micelle water core encourages the development of the reverse micelle NMR method as a generally applicable approach [38]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to classic structure determination, the reverse micelle NMR systems offer a range of benefits in biophysical studies of proteins and nucleic acids such as hydration, temperature and pressure dependent phenomena, ligand binding, confined space effects and so on. The recent observation of substantial nitroxide-mediated dynamic nuclear polarization of the reverse micelle water core encourages the development of the reverse micelle NMR method as a generally applicable approach [38]. …”
Section: Discussionmentioning
confidence: 99%
“…In practice, this provides a two- to three-fold signal-to-noise advantage, which is particularly important in light of the relatively limited concentration of encapsulated protein solutions that can currently be achieved. Looking forward, the recent demonstration that solutions of reverse micelles seem to enable dynamic nuclear polarization in large-volume liquid samples bodes well for overcoming this concentration limitation in the future [38]. …”
Section: Practical Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…RM samples effectively replace ~98% of the aqueous buffer with alkane, thus eliminating this dielectric penalty, allowing very high salt concentrations to be used in the aqueous RM core (Flynn, Mattiello, Hill, & Wand, 2000). Greatly reduced water content also allows dynamic nuclear polarization (DNP) of proteins in a standard volume solution (Valentine, Mathies, Bédard, Nucci, Dodevski, Stetz et al, 2014) though the general utility of this remains to be demonstrated. In addition, the aqueous core of a RM is a confined space that greatly destabilizes extended or unfolded states and drives proteins to the more compact less extensive state.…”
Section: Introductionmentioning
confidence: 99%
“…The phase diagram of reverse micelle surfactants is complex and can be manipulated to result in particles with sufficient anisotropic magnetic susceptibility to result in partial alignment and measureable RDCs (Valentine, Pometun, Kielec, Baigelman, Staub, Owens et al, 2006) (Figure 3). Other long distance restraints can also be obtained using paramagnetic relaxation effects (PRE) (Valentine, et al, 2014) and pseudo-contact shifts (PCS) (O’Brien, et al, 2015). High-resolution structures of proteins in different reverse micelle systems have been solved including ubiquitin in AOT reverse micelles (Babu, Flynn, & Wand, 2001), and oxidized horse cytochrome c in 10MAG/LDAO reverse micelles (O’Brien, et al, 2015) (Figure 4).…”
Section: Introductionmentioning
confidence: 99%